The Human Dimension: Putting the Person into Personalised Medicine. Issue 1 (2nd January 2017) - Horne, Rob
Abstract : Technological advances enabling us to personalise medical interventions at the biological level must be matched by parallel advances in how we support the informed choices essential to patient and public participation. We cannot take participation for granted. To be truly personalised, medicine must take account of the perceptions and capabilities that shape participation. To do this, we need a better understanding of how people perceive personalised medicine and how they judge its value and risks. To realise the promise of 4P medicine we need to personalise at the psychosocial as well as biological dimension, putting the person into personalised medicine.